2022
DOI: 10.3389/fcell.2022.981661
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of transcriptome and chromatin accessibility revealed sequential regulation of potential transcription factors during the brown adipose tissue whitening in rabbits

Abstract: Brown adipose tissue (BAT) represents a valuable target for treating obesity in humans. BAT losses of thermogenic capacity and gains a “white adipose tissue-like (WAT-like)” phenotype (BAT whitening) under thermoneutral environments, which could lead to potential low therapy responsiveness in BAT-based obesity treatments. However, the epigenetic mechanisms of BAT whitening remain largely unknown. In this study, BATs were collected from rabbits at day0 (D0), D15, D85, and 2 years (Y2). RNA-sequencing (RNA-seq) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Based on the lncRNA expression patterns, we found that a small number of mRNAs at D0 and D15 and a large number of mRNAs at D85 and Y2 regulated by lncRNAs involved ceRNA networks, which might suggest that lncRNAs mainly regulate BAT whitening in the later stage of BAT whitening in rabbits. A previous study showed that de novo lipid (DNL) synthesis was a key biological process during BAT whitening in mice [ 12 ], and our previous study showed that DNL-related genes reached the highest expression levels at D85 during BAT whitening [ 29 ]. In this study, the most significantly enriched GO-BP terms by the D85-selective lncRNAs involved ceRNA networks was positive regulation of cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the lncRNA expression patterns, we found that a small number of mRNAs at D0 and D15 and a large number of mRNAs at D85 and Y2 regulated by lncRNAs involved ceRNA networks, which might suggest that lncRNAs mainly regulate BAT whitening in the later stage of BAT whitening in rabbits. A previous study showed that de novo lipid (DNL) synthesis was a key biological process during BAT whitening in mice [ 12 ], and our previous study showed that DNL-related genes reached the highest expression levels at D85 during BAT whitening [ 29 ]. In this study, the most significantly enriched GO-BP terms by the D85-selective lncRNAs involved ceRNA networks was positive regulation of cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…BATs were collected from the interscapular regions of 12 male rabbits at four growth stages of day0 (D0), D15, D85, and 2 years (Y2) (three individuals per stage). These samples were isolated from the same rabbits subjected to our previous RNA-seq study, which revealed the downregulation of UCP1 , COX1 , and PPARGC1A and the upregulation of ACSS2 , ACLY , SNCG , LEP , and CCDC80 [ 29 ] (Figure S 1 A). On the other hand, a well reproducibility among replicates in corresponding group was also found in the previous RNA-seq data [ 29 ] (Figure S 1 B).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations